2021
DOI: 10.32996/ijllt.2021.4.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Smartphones as a Tool for Expediting English Vocabulary Learning: Teachers’ Perceptions of Benefits and Drawbacks‏

Abstract: This study surveyed teachers’ perceptions of the efficiency of utilizing smartphones as a tool for helping EFL students ameliorate their English vocabulary learning. A 27-item questionnaire was administered to 120 teachers working at various state and private secondary schools in Saudi Arabia. Findings revealed that the great majority of teachers (84%) considered smartphones an effective tool for teaching vocabulary. The current study also showed that teaching experience had statistically significant effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Other mobile apps offered just like a conventional flash card with pictures of the words taught, while the other apps conveyed the definitions and instances for writing [7]. The majority of 84% of teachers, have considered using smartphones an effective tool for teaching vocabulary [8]. Mobile apps can be effective tools for vocabulary learning, and it is easy to download to mobile devices for free or at a low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Other mobile apps offered just like a conventional flash card with pictures of the words taught, while the other apps conveyed the definitions and instances for writing [7]. The majority of 84% of teachers, have considered using smartphones an effective tool for teaching vocabulary [8]. Mobile apps can be effective tools for vocabulary learning, and it is easy to download to mobile devices for free or at a low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, from the teacher's side, the use of a smartphone also helps the teacher in the teaching and learning process. Based on the result of the research which was conducted by Kadwa & Alshenqeeti(2020) showed that 84% of the teachers considered that smartphone was an effective tool for teaching vocabulary. This finding was in line with Poláková & Klímová(2020), who stated that mobile learning applications also might help the teacher to access the students' achievement easily and observe them in an authentic and informative way.…”
Section: Introductionmentioning
confidence: 99%